Gender and Tourism Justice: Empowering Women in Indonesia’s Tourism Sector (Indonesian Tourism Justice Review, 2024)
Indonesia’s tourism sector, one of the country's fastest-growing industries, offers significant economic opportunities; however, women remain disproportionately affected by gender inequality within this sector. This paper critically explores how gender dynamics shape women’s experiences in Indonesia’s tourism industry, focusing on employment, income inequality, and access to leadership roles. By analyzing qualitative interviews with female workers in hospitality, tour operations, and local crafts markets, the research identifies key barriers such as wage gaps, sexual harassment, and limited professional advancement. The study highlights initiatives aimed at empowering women, including government policies and non-governmental organizations’ (NGOs) interventions that promote female entrepreneurship and leadership in tourism. Drawing on feminist theory and social justice frameworks, the paper evaluates the effectiveness of these initiatives in addressing gender imbalances and promoting women’s rights within the tourism workforce. The findings suggest that, while progress has been made, more systemic changes are needed to achieve gender equity, including the enforcement of labor rights, the creation of safe workplaces, and greater representation of women in decision-making roles. The paper concludes by offering policy recommendations for improving gender justice in Indonesia’s tourism sector, calling for a more inclusive and gender-sensitive approach to tourism development.